Effect of Two Types of Thoracolumbosacral Brace (With and Without Sensors) on Electromyography Activity of Selected Muscles in People With Thoracic Kyphosis During Typing - AmirAli Jafarnezhadgero; Milad Piran Hamlabadi; Ebrahim Noorian (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims People suffer from neck pain, headache, kyphosis and back pain while working with the computer for a long time, which seems to increase day by day with the advancement of technology. The present study aims to investigate the effect of two types of thoracolumbosacral braces (with and without sensors) on electromyography activity of selected muscles in people with thoracic kyphosis during typing.Methods In this quasi-experimental study, 15 males with thoracic kyphosis volunteered to participate in the study. Subjects performed typing task for one minute at three conditions (with no brace, with a simple brace, and with a brace having sensors). An 8-channel wireless electromyography system was used to record the activity of selected muscles in the upper limb and shoulder area. Repeated measures analysis of variance was used to compare the electrical activity of muscles between different conditions. The significance level was set at 0.05.Results The median frequency of trapezius muscle was significantly lower while using the brace with sensors compared to that without using brace (P=0.005). In median frequency of other muscles, no significant differences were observed among three conditions (P>0.05).Conclusion The use of thoracolumbosacral brace with sensors can reduce the median frequency of trapezius muscle in people with kyphosis. This reduction in median frequency may be related to the passive support of the brace. Reduction of electrical activity in trapezius muscle while using thoracolumbosacral brace can increase the time to reach fatigue.